Disclosure of corporate social responsibility (CSR) and the impact on mining companies - Charina Garis Suryani (The Indonesian Accounting Review, 2013)
Today, financial condition cannot guarantee completely the value of the company inorder to grow continuously. Corporate sustainability will is secured if the companiespay attention to the social and environmental dimensions. With an increasingly criticalsocietal change and being able to exercise social control, they can raise a newawareness of the importance of Corporate Social Responsibility (CSR). Mining industryhas to know that there is appositive correlation between the implementation of CSRand increased appreciation for the international and domestic industry. They have tounderstand that the implementation of CSR not only regard merely as a cost, but alsoa long-term investment for the company. This research aims to examine the effect ofprofitability, leverage, firm size and firm age on CSR disclosure by mining companies.The sample used is mining company listed on the Stock Exchange since 2009 until2011.The conclusion of the this study is leverage, firm size, and firm age have a significanteffect of CSR disclosure by companies but profitability haven’t significanteffect on CSR disclosure by the sample companies.